Red Cell Distribution Width Upon Hospital Admission Predicts Short-Term Mortality in Hospitalized Patients With COVID-19: A Single-Center Experience - Kaufmann, Christoph C.; Ahmed, Amro; Brunner, Ulrich; Jäger, Bernhard; Aicher, Gabriele; Equiluz-Bruck, Susanne; Spiel, Alexander O.; Funk, Georg-Christian; Gschwantler, Michael; Fasching, Peter; Huber, Kurt (Frontiers in Medicine, 2021)
Background: Coronavirus disease (COVID-19) was first described at the end of 2019 in China and has since spread across the globe. Red cell distribution width (RDW) is a potent prognostic marker in several medical conditions and has recently been suggested to be of prognostic value in COVID-19. Methods: This retrospective, observational study of consecutive patients with COVID-19 was conducted from March 12, 2020 to December 4, 2020 in the Wilhelminenhospital, Vienna, Austria. RDW levels on admission were collected and tested for their predictive value of 28-day mortality. Results: A total of 423 eligible patients with COVID-19 were included in the final analyses and 15.4% died within 28 days (n = 65). Median levels of RDW were significantly higher in non-survivors compared to survivors (14.6% [IQR, 13.7– 16.3] vs 13.4% [IQR, 12.7– 14.4), P < 0.001). Increased RDW was a significant predictor of 28-day mortality (crude odds ratio [OR] 1.717, 95% confidence interval [CI] 1.462 – 2.017; P = <0.001), independent of clinical confounders, comorbidities and established prognostic markers of COVID-19 (adjusted OR of the final model 1.368, 95% CI 1.126 – 1.662; P = 0.002). This association remained consistent upon sub-group analysis. Our study data also demonstrate that RDW levels upon admission for COVID-19 were comparable to previously recorded levels before SARS-CoV-2 infection (14.2% [IQR, 13.3 – 15.7] vs 14.0% [IQR, 13.2 – 15.1]; P = 0.187). We also found that patients with a more recent onset of symptoms had higher levels of RDW upon admission (P < 0.001). Conclusions: In this population, RDW was a significant, independent prognostic marker of short-term mortality in patients with COVID-19.